Characterization and cytotoxic activity on glial cells of alkaloid-enriched extracts from pods of the plants prosopis flexuosa and prosopis Nigra (Fabaceae) - Cholich, Luciana Andrea (2021)
Fil: Cholich, Luciana Andrea. Universidad Nacional del Nordeste. Facultad de Ciencias Veterinarias; Argentina.